PENGARUH LINGKUNGAN KERJA NON FISIK TERHADAP MOTIVASI INTRINSIK DAN KEPUASAN KERJA DI DINAS PENDAPATAN DAERAH BADUNG - Sentosa, I Made Handy; Riana, I Gede (E-Jurnal Manajemen, 2018)
The purpose of this study is to determine the effect of non physical work environment on intrinsic motivation and employee job satisfaction, and influence the influence of intrinsic motivation on job satisfaction of employees at Badung Revenue Service Office. Sources of data used in this study are primary and secondary data. The population to be used in this study is as many as 187 employees. The sample in the study is the entire population as the sample. Data collection techniques using questionnaires. Technique of data analysis using path analysis (path analysis). The result of the research shows that the non-physical work environment has a positive and significant influence on job satisfaction on the employee in the Badung Mangusada regional income office. Non-physical work environment has a positive and significant influence on intrinsic motivation on employees in the Badung Mangusada Regional revenue service. Intrinsic motivation has a positive and significant influence on job satisfaction at employees in the Badung Mangusada Regional revenue service.